THE IMPACT OF THE OPERATION OF THE DURI SELATAN TOLL GATE ON LAND COVER IN PINGGIR SUB-DISTRICT, BENGKALIS REGENCY - Nugraha, Aldyth Dzaki; Endrawati Fatimah; Wisely Yahya (Universitas Trisakti, 2024)
The presence of transportation infrastructure has a positive impact on increasing the mobility of people and goods. Another impact that usually accompanies it is the acceleration of changes in land use or land cover. This research is motivated by the construction of the Pekanbaru-Dumai Toll Road (Permai) in Riau Province. The study area is focused around the South Duri Toll Gate, precisely in the Pinggir District, Bengkalis Regency. The selection of the study area is based on the consideration that this toll gate location is only 3 km away from the Balairaja Wildlife Sanctuary and the Sebanga Elephant Training Center Wildlife Sanctuary, which are categorized as areas that should be protected. The aim of this research is to identify the differences in land cover changes in the 5 years before (2012-2017) and 5 years after (2017-2022) the operation of the South Duri Toll Gate. The analysis methods used are spatial analysis and descriptive statistical methods. The results show that both before (2012-2017) and after (2017-2022) the operation of the South Duri Toll Gate, there has been a conversion of forest land at a rate of around 400 ha per year. The majority of forest land cover has changed to plantation and agricultural land. In other words, after 5 years of operation, the presence of the South Duri Toll Gate has not or has not yet had a significant impact on land cover changes in its vicinity.